Metabolomics: Paving the path for personalized periodontics - A literature review - Antarleena Sengupta; Ashita Uppoor; Manjunath Bandu Joshi (Wolters Kluwer Medknow Publications, 2022)
The pathogenesis of periodontal disease is governed by a multitude of factors ranging from the macroscopic to the microscopic scale. Among the factors that constitute the etiological agents of the disease, a major element is the role played by the body's metabolome-i.e., the complete collection of microscopic molecules and metabolic products of cells and tissues in the body. Being of a regulatory nature, the interplay of these molecules exerts a considerable effect on the development as well as the progression of disease, which differs in each individual based on their phenotype. Exploring this connection and application into the field of diagnostic as well as prediction of risk for periodontitis will ultimately result in a personalized standard of care for patients in the future.